Race to Revolution : The U.S. and Cuba during Slavery and Jim Crow - Horne, Gerald (Book collections on Project MUSE., 2014)
"The histories of Cuba and the United States are tightly intertwined and have been for at least two centuries. In Race to Revolution, historian Gerald Horne examines a critical relationship between the two countries by tracing out the typically overlooked interconnections among slavery, Jim Crow, and revolution. Slavery was central to the economic and political trajectories of Cuba and the United States, both in terms of each nation's internal political and economic development and in the interactions between the small Caribbean island and the Colossus of the North. Horne draws a direct link between the Black experiences in two very different countries and follows that connection through changing periods of resistance and revolutionary upheaval. Black Cubans were crucial to Cuba's initial independence, and the relative freedom they achieved helped bring down Jim Crow in the United States, reinforcing radical politics within the Black communities of both nations. This in turn helped to create the conditions that gave rise to the Cuban Revolution which, on New Years' Day in 1959, shook the United States to its core. Based on extensive research in Havana, Madrid, London, and throughout the U.S., Race to Revolution delves deep into the historical record, bringing to life the experiences of slaves and slave traders, abolitionists and sailors, politicians and poor farmers. It illuminates the complex web of interaction and influence that shaped the lives of many generations as they struggled over questions of race, property, and political power in both Cuba and the United States"--